Dietary Supplements as a Major Cause of Anti-doping Rule Violations - Lauritzen, Fredrik (Frontiers in Sports and Active Living, 2022)
Dietary supplements encompass a large heterogenic group of products with a wide range of ingredients and declared effects used by athletes for a multitude of reasons. The high prevalence of use across all sports and level of competition, combined with the well documented risks of such products containing prohibited substances have led to several doping cases globally. Despite being a considerable concern and persistent focus of sport organizations and anti-doping agencies, the magnitude of anti-doping rule violations associated with supplement use is not well known. This study examines 18-years of doping controls of a national anti-doping program to determine the relationship between the presence of prohibited substances in athlete´s doping samples and the use of dietary supplements. In 26% (n = 49) of all the analytical anti-doping rule violation cases in the period 2003-2020 (n = 192), the athlete claimed that a dietary supplement was the source of the prohibited substance causing an adverse analytical finding. Evidence supporting this claim was found in about half of these cases (n = 27, i.e. 14% of all analytical ADRV´s). Stimulants were the most prevalent substance group linked to supplements (n = 24), of which methylhexanamine was associated with 16 cases. High risks products were Multi-ingredient pre-workout supplements (n = 20), and muscle-building supplements (n = 5). Anti-doping organizations should develop strategies on how to assist athletes to assess the need, assess the risk and assess the consequences of using various dietary supplements.